Evolution of 2D tin oxides on the surface of molten tin. Issue 17 (26th January 2018) - Atkin, P.; Orrell-Trigg, R.; Zavabeti, A.; Mahmood, N.; Field, M. R.; Daeneke, T.; Cole, I. S.; Kalantar-zadeh, K.
Abstract : The exfoliation of two dimensional (2D) oxides, established on the surface of specific liquid metals, has recently been introduced. Abstract : The exfoliation of two dimensional (2D) oxides, established on the surface of specific liquid metals, has recently been introduced. One such liquid metal is molten tin, which forms a variety of surface 2D oxides. However, the development behaviour of these surface tin oxides is still unknown. Here the evolution of stoichiometry and thickness from single-layer SnO to highly oxidised multi-layer SnO2 in ambient oxygen is explored.